Feeding Coparenting Scale (FCS): Validity and Reliability Study of the Turkish Adaptation - Coskun, Ayfer Beyaz; Ozer, Sehriban Duyar (Wiley, 2025)
Parental attitudes play an important role in the development of nutritional behaviour in children. In this context, the Feeding Coparenting Scale (FCS) is among the scales that can be used to evaluate the attitudes of parents towards the nutrition of their children. This study was planned to evaluate the validity and reliability of the FCS scale in the Turkish population and was conducted in two stages. In the pilot study, the suitability of the scale for validity analysis was evaluated with 34 parents. Then, in the second stage, confirmatory factor analyses of the FCS scale were conducted with 230 participants. Since the item-total score correlation values of 11 out of 13 items in the scale were high, 11 items were included in the factor analysis. Confirmatory Factor Analysis provided 11 items and 3-factor structural validity. As a result, it is thought that the Turkish form of the FCS scale can be a valid scale that can be used in the Turkish society with acceptable compliance in evaluating how mothers and fathers work together in the field of child nutrition.
Keywords: early childhood; feding coparenting; nutrition; reliability; validation